The flaming feet and other essays : the dalit movement in India - Nagaraj, D. R. (Doḍḍabaḷḷāpura Rāmayya), 1954-1998.; Shobhi, Prithvi Datta Chandra (Ranikhet : Permanent Black ; Bangalore : Distributed by Orient Blackswan, 2010)
Chiefly with reference to Karnataka, India.
Includes bibliographical references (p. [244]-250) and index.
Keywords: Dalits -- Political activity -- India -- Karnataka; Kannada literature -- Dalit authors -- History and criticism; Karnataka (India) -- Social conditions; Karnataka (India) -- Politics and government